Oxidative stress induces Ser 2 dephosphorylation of the RNA polymerase II CTD and premature transcription termination. Issue 5 (20th October 2021) - Yamazaki, Takashi; Liu, Lizhi; Manley, James L.
ABSTRACT: The C-terminal domain (CTD) of the largest subunit of RNA polymerase II (Pol II) consists of YSPTSPS heptapeptide repeats, and the phosphorylation status of the repeats controls multiple transcriptional steps and co-transcriptional events. However, how CTD phosphorylation status responds to distinct environmental stresses is not fully understood. In this study, we found that a drastic reduction in phosphorylation of a subset of Ser2 residues occurs rapidly but transiently following exposure to H2 O2 . ChIP analysis indicated that Ser2-P, and to a lesser extent Tyr1-P was reduced only at the gene 3' end. Significantly, the levels of polyadenylation factor CstF77, as well as Pol II, were also reduced. However, no increase in uncleaved or readthrough RNA products was observed, suggesting transcribing Pol II prematurely terminates at the gene end in response to H2 O2 . Further analysis found that the reduction of Ser2-P is, at least in part, regulated by CK2 but independent of FCP1 and other known Ser2 phosphatases. Finally, the H2 O2 treatment also affected snRNA 3' processing although surprisingly the U2 processing was not impaired. Together, our data suggest that H2 O2 exposure creates a unique CTD phosphorylation state that rapidly alters transcription to deal with acute oxidative stress, perhaps creating a novel "emergency brake" mechanism to transiently dampen gene expression.